KUALITAS BUTIR SOAL SEBAGAI FONDASI EVALUASI PEMBELAJARAN: SEBUAH KAJIAN TEORETIS TENTANG PENGECOH, KESUKARAN, DAN DAYA PEMBEDA - Mhd Ali Wardana; Masyitoh Hasibuan; Nur Asyifa; Aisyah Amini; Yusro Layla (Sasangga: Jurnal Pendidikan dan Pembelajaran, 2026)
This research focuses on examining the quality of question items in learning evaluation tools based on three main criteria: the effectiveness of the trickster, the level of difficulty, and the ability to distinguish. A literature review approach was used for this study, by exploring a variety of relevant academic books and articles related to educational assessment. The analysis is conducted in a structured manner, combining theoretical perspectives and insights from previous studies to gain an in-depth understanding of the attributes of high-quality question items.The findings of the study show that the effectiveness of the question items is greatly influenced by how well the wrong answer choices are designed, the distribution of difficulty levels, and the ability to distinguish between students with different abilities. Effective question items usually have a balanced level of difficulty, strong discriminating abilities, and incorrect answer choices that fit the intended purpose. Conversely, question items that are too low or too high in difficulty, along with incorrect answer choices that fail to fulfill their function, will compromise the overall reliability and validity of the assessment tool. These results highlight the important role of question item analysis in the educational assessment process